Attitudes towards English Medium Instruction Courses among Second Language Learners in Relation to Learning Anxiety and Learning Achievement - Che Ghani, Nurul Farhani Binti (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2018)
The purpose of this paper was to examine second language learners’ attitudes towards English Medium Instruction (EMI) courses at University of Selangor (UNISEL) in Malaysia affectively, behaviorally and cognitively. This study also investigated students’ learning anxiety and students’ learning achievement towards EMI courses. This study employed ABC Model of Attitudes (1998) as guidelines to investigate learners’ attitudes towards EMI courses. 100-degree students form Faculty of Science and Information Technology (FSIT) participated in the study by completing a questionnaire of English Medium Instruction courses. A quantitative method was employed to analyze the collected data, performing statistical procedures of descriptive statistic and Pearson correlation using SPSS. The major findings of the study were as follows: (1) most participants demonstrated positive attitudes towards English medium Instruction courses affectively, behaviorally and cognitively, (2) there was no significant relationship between students’ learning anxiety and students’ learning achievement towards EMI courses. It was due to the ways lecturers delivering EMI courses to the students. This situation happened when the way their lecturers conducted the lesson in English medium setting might help the students reduce their learning anxiety of the lesson. In other words, the level of their anxiousness in learning EMI courses depends on how their lecturers deliver the subject during teaching and learning process. Finally, some pedagogical implications that would help tap the students’ attitudes and achievement were demonstrated.Keywords: English Medium Instruction, attitudes, learning anxiety, learning achievement